A dimensão formativa do PIBID para o professor supervisor - Maria Alice Braga Camilo da Costa (2016)
The practice of teacher of basic school indicates the need to expand moments of reflection about your do, since everyday is strong demands, lacking time to do so. The experience in PIBID/FAE/UFMG provided moments of meeting, socializing and training of undergraduates, but drew attention that this participation is a possibility of in-service training for math supervisors teachers (basic school) and, consequently, higher professional development. We asked if the professor of elementary school has had in PIBID this opportunity and, before it, becomes a co-trainer of undergraduates participating, along with the coordinator university professor. Our research was developed through observation of meetings of the Mathematics area group PIBID, conducting a meeting with supervisors in several areas where we put the discussion on the wheel on the formative dimension of their participation and also about their status as active co-treiner of future teachers. For a focus on the specific opinions of mathematics teachers, we turn to the reports prepared by them. Our finding confirms the participation of PIBID supervisors as a process that favors their training and their professional development, from reflection on practice, access to topics and innovations in contact with the university, and supervisors indicated the timing of the weekly meeting as the most important in this regard. In addition, supervisors see gradually in the position of co-trainers, feeling like reference in their practices for future teachers, assuming the values of their profession and their knowledge. The product of labor will be a meaningful and formative text to present to supervisors PIBID as supporting their processes of reflection and training.